The positive effects of insurance on livestock production and grassland ecological benefits: evidence from Qinghai-Tibet Plateau of China - Zeng Tang; Menglin Zhao; Haibin Dong; Yubing Fan; Ying Liu; Funing Li; LIjia Wang; Xiangyang Hou (Ecology and Society, 2025)
In this study empirically we investigate the effects of livestock insurance on livestock production in the Qinghai-Tibet Plateau (QTP), a traditional pastoral area in China, employing a dataset comprising 216 households. The Propensity Score Matching (PSM) approach is employed to correct for self-selection bias. The results show that livestock insurance has a positive and significant impact on livestock production in the QTP. Insured households allocate an additional 5.848 person-months to livestock production compared to uninsured households. On average, the livestock income of insured households increases by 10,900 CN¥. Additionally, livestock insurance stimulates a 6.483 percentage point increase in off-take rates by mitigating household production risks. Consequently, this can alleviate grazing pressure and contribute to the conservation of grassland in the QTP. The heterogeneous analysis reveals that livestock insurance provides greater benefits to low-income households, thus contributing to poverty alleviation and reducing income disparity in the QTP. Overall, the evidence presented in this paper highlights the favorable ecological and well-being effects of livestock insurance in the QTP.